A reconsideration of the EWOM construct in restaurant research: what are we really measuring?. Issue 11 (28th September 2020) - Line, Nathaniel Discepoli; Hanks, Lydia; Dogru, Tarik
Abstract : Purpose: With the proliferation of internet-based communication channels, understanding how restaurant consumers engage in electronic word of mouth (EWOM) has become an important field of academic pursuit. However, while communication channels have become more numerous and complex, the methods used to operationalize the attendant EWOM behaviors on these channels have remained relatively simplistic. Accordingly, the purpose of this paper is to consider existing methods of measuring restaurant EWOM in terms of their face validity in the contemporary communications landscape. Design/methodology/approach: This study uses a total of six independent surveys that use various combinations of sampling, methodological and analytical approaches to demonstrate, measurement, social media, methodology, user-generated content, EWOM, electronic word of mouth the multiple problems associated with the measurement of restaurant EWOM as a latent construct. Findings: The results suggest that the current methods for measuring EWOM are indeed outdated, indicating the need for a more nuanced approach to the academic pursuit of EWOM behavior. Research limitations/implications: The existing methods of measuring restaurant EWOM are found to be invalid for many reasons. These methods of measuring EWOM should be abandoned in favor of channel-specific operationalizations that control for previous behavior and respondents' account access at a minimum. Originality/value: As its inception, many studies have operationalized restaurant EWOM as an intention-based construct used to measure an individual's likelihood to communicate information about hospitality experiences "online." While such measures were no doubt valid in the early years of EWOM research, the research is the first to criticize the face validity of this approach in terms of its relevance in the contemporary communications environment.